N+-4=-11

Simple and best practice solution for N+-4=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for N+-4=-11 equation:


Simplifying
N + -4 = -11

Reorder the terms:
-4 + N = -11

Solving
-4 + N = -11

Solving for variable 'N'.

Move all terms containing N to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + N = -11 + 4

Combine like terms: -4 + 4 = 0
0 + N = -11 + 4
N = -11 + 4

Combine like terms: -11 + 4 = -7
N = -7

Simplifying
N = -7

See similar equations:

| (32b)^(2/3) | | 3•5/13 | | (3x+5)(5x-2)=0 | | 4+2(7r-4)=-116 | | 2=0.15x^2+1 | | (((2z)^(1/5))^4)/(z^(1/20)) | | 4+2(7r-r)=-116 | | 5=0.55x^2+1 | | (((2z)^(1/5))^4)/z^(1/20) | | 2.70=0.55x^2+1 | | -2x-3y=-5 | | -5(4n-4)=40 | | -5h=-20 | | 4(x-1)=2(-x) | | 4p^2+11p-45=0 | | 6(2v-2)=96 | | 40b+10=210 | | (2x+10)+5x+140= | | 3(8-4x)=84 | | 4x-13-35=0 | | 3x+90=450 | | 2(x+5)(x-1)= | | 7+9+n=-9+2n+n | | 4*x^2+4*y^2-y^3=0 | | 4c-36=-8 | | y+26-8=40 | | 93=16-5p | | -12x-4=56 | | 6k-15=-33 | | 5x^2+y^2=21 | | 6x-3=17+4x | | 12/21 |

Equations solver categories